2017
DOI: 10.1111/jocn.13914
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to serious adverse events in nursing homes

Abstract: Aims and objectives: To identify the most common serious adverse events that occurred in nursing homes and their most frequent contributing factors to the improvement of safe nursing care.Background: There is a need to improve safe nursing care in nursing homes. Resi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 37 publications
3
102
0
2
Order By: Relevance
“…Most of the study participants did not expect shared living in 1 place and experienced high stress and pain from such reality, which is very different from what they expected for their retired life. This mostly concurs with the results of multiple studies (Andersson et al, ; Kong, ; Statistics Korea, ; Um, ) on the lives of elderly people living in residential facilities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most of the study participants did not expect shared living in 1 place and experienced high stress and pain from such reality, which is very different from what they expected for their retired life. This mostly concurs with the results of multiple studies (Andersson et al, ; Kong, ; Statistics Korea, ; Um, ) on the lives of elderly people living in residential facilities.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is also a living space that oversees the admitted elderly people and provides them with life‐sustaining treatment. Such space can be an inhabited world with relational conversations where the elderly people's daily lives can unfold (Andersson, Frank, Willman, Sandman, & Hansebo, ; Chang, ), and preceding studies showed that daily stress increased the idea of suicide in the admitted elderly people (Andersson et al, ; Jo, ). Also, in a survey on the expression of cognitive/behavioural disorders and psychological problems, the elderly people admitted to long‐term care hospitals showed the highest scores in severe depression, anxiety, and the repetitive idea of suicide (Kim, Jung, & Lee, ; Palese et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regulations concerning the quality of care in health and social services were issued in 1997 and revised in 2003 (Kjøs et al, ; Norwegian Ministry of Health & Care Services, ). Andersson, Frank, Willman, Sandman, and Hansebo () maintained that the lack of competence was one of the most common factors contributing to serious adverse events. It seems that the challenge lies both in creating an understanding of the duty to implement internal control and to fulfil this obligation, which applies at all levels, from the municipal central management to where the patient receives the service (The Office of the Auditor General, ).…”
Section: Leadership and Quality Of Carementioning
confidence: 99%
“…Although the role of the RN is specified in guidelines, with facilities in the United States required to have at least one on site for at least eight hours every day, these guidelines are commonly not adhered to (Geng, Stevenson, & Grabowski, 2019) and numbers are likely inadequate to meet needs. Internationally, the quality of patient outcomes has been challenged and often attributed to staffing or resources (Andersson, Frank, Willman, Sandman, & Hansebo, 2018;Spilsbury, Hewitt, Stirk, & Bowman, 2011). Geng and colleagues studied a number of facilities and found that greater than half of the facilities met the expected staffing level less than 20% of the time.…”
mentioning
confidence: 99%